Piezoelectric Actuators Principles, Design, Experiments and Applications - Huang, Hu; Li, Jianping (IntechOpen, 2021)
Taking advantage of high resolution, rapid response, and compact structure, piezoelectric actuators are widely employed for achieving precision positioning in both scientific research and industrial application. With the development of science and technology, the requirements for precision positioning are increasing. Accordingly, great efforts have been made to improve the performances of piezoelectric actuators, and significant progress has been achieved. This book discusses some recent achievements and developments of piezoelectric actuators, in terms of piezoelectric material, driving principle, structural design, modeling, and control, as well as applications.